1999
DOI: 10.1093/brain/122.5.799
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome in patients with epilepsy and dual pathology

Abstract: High-resolution MRI can detect dual pathology (an extrahippocampal lesion plus hippocampal atrophy) in about 5-20% of patients with refractory partial epilepsy referred for surgical evaluation. We report the results of 41 surgical interventions in 38 adults (mean age 31 years, range 14-63 years) with dual pathology. Three patients had two operations. The mean postoperative follow-up was 37 months (range 12-180 months). The extrahippocampal lesions were cortical dysgenesis in 15, tumour in 10, contusion/infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
125
1
10

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(138 citation statements)
references
References 25 publications
2
125
1
10
Order By: Relevance
“…[7][8][9][10] In a subset of these tumors, which are generally low-grade glial or glioneuronal neoplasms, multiple pathologies, which potentially may contribute to the genesis of these seizures, are identifiable (dual pathology). [11][12][13][14][15][16] Among these, there is a well-established association of certain neoplasms with malformations of cortical development (cortical dysplasia), particularly dysembryoplastic neuroepithelial tumors and gangliogliomas. [17][18][19][20] The purpose of this study is to systematically review one institution's experience with neoplasms associated with identifiable coexistent pathology arising in the setting of chronic epilepsy.…”
mentioning
confidence: 99%
“…[7][8][9][10] In a subset of these tumors, which are generally low-grade glial or glioneuronal neoplasms, multiple pathologies, which potentially may contribute to the genesis of these seizures, are identifiable (dual pathology). [11][12][13][14][15][16] Among these, there is a well-established association of certain neoplasms with malformations of cortical development (cortical dysplasia), particularly dysembryoplastic neuroepithelial tumors and gangliogliomas. [17][18][19][20] The purpose of this study is to systematically review one institution's experience with neoplasms associated with identifiable coexistent pathology arising in the setting of chronic epilepsy.…”
mentioning
confidence: 99%
“…Dual pathology does not merely indicate the anatomical coexistence of HS with an extrahippocampal lesion, but also pathophysiological mechanisms such as the kindling phenomenon and secondary hippocampal epileptogenesis [9,10,11,12]. Dual pathology is almost exclusively found in patients with congenital extrahippocampal lesions or occurs early in life, suggesting that the hippocampus is more vulnerable and more likely to develop HS in early childhood [3].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Salanova et al [3] showed that resection of both lesions led to an excellent outcome, with 70.2% of patients becoming seizure-free and 21.6% having only rare seizures, while none of the patients with non-resected extrahippocampal lesions became seizure-free. Furthermore, Li et al [11] demonstrated that 73% of patients with both lesions resected became seizure-free, compared with 20% of patients with only the medial temporal structures resected and 12.5% of patients with only the extrahippocampal lesion resected. The investigators thus concluded that removal of both lesions is the best surgical approach, and should be considered whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…The injuries diagnosis associated with MTS has great clinical importance, due to its impact in response to clinical treatment 71 and programming of surgery 72,73 . The association of MTS plus another lesion out of the hippocampus constitutes dual pathology 73,74 , which was seen in 5 to 30% of patients with focal epilepsy and drug-resistant seizures 74 . MTS may be associated with several other pathologies, such as MCD, slow growth tumors, vascular malformations, porencephaly, and gliosis [72][73][74][75][76] .…”
mentioning
confidence: 99%